Blood pressure monitoring in cardiovascular medicine and therapeutics - White, William B. (Contemporary cardiology, 2001)
I Techniques for Out-of-Office Blood Pressure Monitoring -- 1 Self-Monitoring of Blood Pressure -- 2 Evaluation of Journals, Diaries, and Indexes of Worksite and Environmental Stress -- 3 Electronic Activity Recording in Cardiovascular Disease -- 4 Ambulatory Monitoring of the Blood Pressure: Devices, Analysis, and Clinical Utility -- II Concepts in the Circadian Variation of Cardiovascular Disease -- 5 Circadian Rhythm and Environmental Determinants of Blood Pressure Regulation in Normal and Hypertensive Conditions -- 6 Circadian Variation of the Blood Pressure in the Population at Large -- 7 Importance of Heart Rate in Determining Cardiovascular Risk -- 8 Sodium, Potassium, the Sympathetic Nervous System, and the Renin—Angiotensin System: Impact on the Circadian Variability in Blood Pressure -- 9 Prognostic Value of Ambulatory Blood Pressure Monitoring -- 10 Circadian Rhythm of Myocardial Infarction and Sudden Cardiac Death -- 11 Seasonal, Weekly, and Circadian Variability of Ischemic and Hemorrhagic Stroke -- III Twenty-Four-Hour Blood Pressure Monitoring and Therapy -- 12 Cardiovascular Chronobiology and Chronopharmacology: Importance of Timing of Dosing -- 13 Advances in Ambulatory Blood Pressure Monitoring for the Evaluation of Antihypertensive Therapy in Research and Practice.